Katekese Tentang Santa Maria Menurut Marialis Cultus Artikel 16-23 Sebagai Model Gereja - Lumban Tobing, Ona Sastri; Tarigan, Thomas Natalisa (IN VERITATE LUX, 2023)
A Church teaching that presents more specifically Mary as a model in divine worship is Marialis Cultus. This apostolic letter, promulgated by Pope Paul VI on February 2, 1974, aims to promote the veneration of the Blessed Virgin Mary especially in divine worship. The Marialis Cultus clearly shows the virtues of the virgin Mary, namely humility which is shown by listening to the Word of God and carrying it out, always praying and expressing her hopes to God. This research uses a literature study approach by collecting various primary and secondary references related to the Marialis cultus document, catechesis on Mary as a model of the Church and analyzing the text and context of the Catholic Church today regarding the implementation of catechesis on Mary. Data analysis techniques are data reduction, data display and conclusion drawing from various references used. The findings in this study are that the Church sees that the actual situation carried out by the people is really concerning, for example: The people have not fully opened themselves to God, humility has not been truly realized so that some people have not listened to the word and implemented it, or listened only to the mind not to the heart, praying just praying without effort and perseverance. So that one solution to answer the situation of this kind of people is the catechesis of the people about Mary which is sourced from the Marialis Cultus document.